Perencanaan Anggaran dan Analisis Kelayakan Investasi Pembangunan Rumah Tinggal Tipe 36 Sebagai Rumah Sewa (Ditinjau dari NPV, IRR, dan Payback Period) - Iqbal Haqi; Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the budget planning and investment feasibility of constructing Type 36 residential units to be used as rental housing, using the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) indicators. The method used is an empirical study with a quantitative approach that integrates construction engineering and engineering economics analysis. The research stages included calculating the volume of work, preparing a Cost Budget Plan based on a Unit Price Analysis, preparing cash flow projections over the investment’s lifespan, and evaluating financial feasibility using the concept of the time value of money. The results show that the initial investment required for constructing a Type 36 house is Rp325,000,000, with the majority of costs attributed to structural work and masonry. Cash flow simulations demonstrate the project’s ability to generate stable rental income throughout the investment period. The feasibility analysis yielded a Net Present Value (NPV) of Rp29,617,428, an Internal Rate of Return (IRR) of 12.84%, and a Payback Period of 8.4 years. These values meet the criteria for a viable investment because they generate positive economic value added, a rate of return higher than the minimum acceptable rate of return (MARR) of 10%, and a payback period that remains within the investment horizon.